Synthesis of mesoporous silica material with ultra-large pore sizes and the HDS performance of dibenzothiophene - Song, S.; Zhou, X.; Duan, A.; Zhao, Z.; Chi, K.; Zhang, M.; Jiang, G.; Liu, Jian; Li, J.; Wang, X. (Elsevier BV, 2016)
© 2016 Elsevier Inc. Ultra-large mesoporous silica materials using different micelle expanders including hexane, cyclohexane, 1,3,5-triisopropylbenzene and 1,3,5-triethylbenzene, have been successfully synthesized by the template of polymer surfactant of P123 (Aldrich, EO20PO70EO20). Among all the used micelle expanders, highly ordered cubic mesoporous silica material (SBA-16@hexane) with ultra-large pore size was obtained by using hexane. All the obtained samples were well characterized by small-angle X-ray scattering (SAXS), transmission electron microscopy (TEM), nitrogen adsorption-desorption, UV-vis diffuse reflectance spectroscopy (DRS), H2-TPR, pyridine-FTIR, 27Al MAS NMR, GC-MS and Raman. The synthesis mechanism was also proposed. Compared with the conventional SBA-16 (6.31 nm) synthesized taking polymer surfactant of F127 (propylene oxide block copolymer) as the template, the as-synthesized SBA-16@hexane had a pore diameter of 15.1 nm with a highly ordered mesostructure, which was the largest one among all the reported pore sizes of SBA-16 materials. The corresponding hydrodesulfurization (HDS) catalysts of NiMo/Al-SBA-16@hexane, NiMo/?-Al2O3, and NiMo/Al-SBA-16 were prepared by using different supports respectively, furthermore, their HDS performances were evaluated adopting dibenzothiophene (DBT) as the probe reactant. The DBT HDS efficiencies over these catalysts followed the order: NiMo/Al-SBA-16@hexane > NiMo/?-Al2O3 > NiMo/Al-SBA-16. The high activity of NiMo/Al-SBA-16@hexane can be attributed to the superior diffusivity of the novel support of SBA-16@hexane with ultra-large pore size.